The Use of Public Diplomacy Tools In Uzbekistan’s Foreign Relations - Odiljonovich, Ismatullaev (Buletin Antropologi Indonesia, 2025)
This article analyzes cultural cooperation and cultural diplomacy, which are among the key areas in the relations between the Republic of Uzbekistan and European countries. The author attempts to show that these relations are being actively demonstrated through various cultural fields ‒ particularly with the developed countries of the European Union such as Germany, Italy, France, and the United Kingdom ‒ by organizing artist exhibitions, photo exhibitions in museums, and displays of traditional folk arts, including ceramic art. The author has also attempted to put forward their own recommendations for further expanding the efforts being carried out in this direction. The article makes effective use of materials from the National Archive of Uzbekistan and the periodical press.